Pattern of Contrast Sensitivity Changes in Acute Central Serous Chorioretinopathy - Preeyachan Lourthai; Patama Bhurayanontachai (Journal of Ophthalmology, 2017)
Purpose. To evaluate contrast sensitivity (CS) changes in acute central serous chorioretinopathy (CSC). Methods. Visual acuity (VA), CS, and subretinal fluid (SRF) were evaluated monthly for 6 months. Treatment was considered at 3 months in case of persistent SRF. Results. Twelve of 20 eyes (60%) had spontaneous SRF resolution within 4 months. Five of 8 patients with delayed SRF resolution received either focal laser or photodynamic therapy. The CS was impaired in all spatial frequencies at baseline. There was a negative correlation between the baseline SRF thickness and CS at 3 and 6 cycles per degree (cpd). The CS improved significantly at the time of fluid resolution (p=0.001) and continued to improve in 3 and 6 cpd. The CS at 6 cpd did not recover if compared to a normal fellow eye at 6 months (p=0.018). The CS of 12 cpd at 6 months was superior in the spontaneous resolution group. Conclusion. The impaired CS gradually improved as the SRF reduced at all spatial frequencies. CS at 3 and 12 cpd continued to improve after complete fluid resolution. Despite an excellent final VA, the CS at 6 months did not regain its normal value.